2015
DOI: 10.1080/01496395.2015.1014914
|View full text |Cite
|
Sign up to set email alerts
|

Nano Calcium Aluminum Mixed Oxide: A Novel and Effective Material for Defluoridation of Drinking Water

Abstract: In the present study Nano Calcium-Aluminium mixed oxide material (NCAMO) was synthesized by solution combustion method in 1:1, 1:2, 4:1, 3:2 molar ratios of Calcium and Aluminum nitrates as oxidizers and urea as fuel for an efficient adsorption of fluoride from drinking water.Molar composition of 1:1 ratio was found to exhibit better adsorption properties and the same Downloaded by [University of Birmingham] at 02:47 23 March 2015 A c c e p t e d M a n u s c r i p t 2 was characterized by XRD, FESEM, and FTIR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Moreover q e experimental and q e calculated values, for the pseudo second order model were close to each other. Hence, the pseudo-second-order model was a better descriptor of the adsorption kinetics of fluoride ion by nano sized c-alumina similar results were reported earlier (Prathibha et al 2015). These results indicated that the overall rate of the fluoride ion adsorption was most likely to be governed by the chemisorption process.…”
Section: Equilibrium Time and Adsorption Kineticssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover q e experimental and q e calculated values, for the pseudo second order model were close to each other. Hence, the pseudo-second-order model was a better descriptor of the adsorption kinetics of fluoride ion by nano sized c-alumina similar results were reported earlier (Prathibha et al 2015). These results indicated that the overall rate of the fluoride ion adsorption was most likely to be governed by the chemisorption process.…”
Section: Equilibrium Time and Adsorption Kineticssupporting
confidence: 85%
“…(2) Occurrences of adsorption on homogeneous sites of the adsorbent and (3) adsorbed molecules do not interact with each other. ''Langmuir isotherm is applied when adsorption is limited to monolayer formation of adsorbate on the surface of adsorbent'' (Prathibha et al 2015). The most popular linear expression of isotherm is as follows:…”
Section: Adsorption Isotherm Studymentioning
confidence: 99%
“…The peaks appeared at~874 cm −1, and at~1425 cm −1 (Figure 3b-d) can be assigned to the vibration of Ca-O species [32]. The bands due to O-H stretching vibration at~1629 cm -1 [34] and O-H bending vibration at~3459 cm −1 [29] were observed in all spectra. The O-H stretching and bending vibrations depicted surface adsorbed water, which was ascribed to the formation of aluminum oxide hydroxide (AlOOH) and calcium hydroxide (CaOH 2 ) on the surface of COMA [35].…”
Section: Characterization Of the Adsorbentmentioning
confidence: 78%
“…The EDX spectrum of COMA before the adsorption indicates the fact that the loading of calcium on the surface of mesoporous alumina was successful. ESEM analysis of COMA after adsorption of fluoride showed a flake-like structure (Figure 2c), which could be attributed to the formation of aluminum and calcium salts with fluoride [34]. EDX analysis confirmed the presence of aluminum (39.4%), oxygen (45,2%), calcium (6.4%), and the adsorbed fluoride (4.1%) on the surface of the COMA (Figure 2c).…”
Section: Characterization Of the Adsorbentmentioning
confidence: 94%
“…Excessive fluoride in the human body can mineralize calcium hydroxyphosphate to calcium fluorophosphate, which causes a significant change in the fluoride-phosphorus ratio resulting in spurs, periosteal hyperplasia, osteoporosis, osteosclerosis, and bone deformation [3,4]. Long-term intake of high-fluoride food by children will result in enamel hypoplasia, tooth damage, and fluoride deposition, causing a series of deformities in the bones [5,6]. The World Health Organization (WHO) stipulates that the maximum fluoride concentration within drinking water should be 1.5 mg L -1 [7]; however, this is exceeded in some developing countries, especially in tropical countries.…”
Section: Introductionmentioning
confidence: 99%